Analisis Beban Kerja Fisiologis dan Psikologis Menggunakan Metode Cardiovascular Load dan NASA TLX di PJT II Jatiluhur - Muhammad Ali Akbar; Rizky Fajar Ramdhani; Sri Nuraeni (Universitas Mercu Buana, 2021)
Perum Jasa Tirta II is a State-Owned Enterprise (BUMN) in the form of a Public Company engaged in providing raw water and electricity for the public benefit this Perum Jasa Tirta II, and there are various units. One of them is the Jatiluhur Tourism and AMDK Business Unit, which produces various types of demineralized drinking water, namely gallons, 600 ml bottles, 330 ml bottles, and 240 ml cups. The implementation of 3 shifts to meet production targets and activities carried out manually at a 40 m / s in a standing position and a 5 second cycle time process is one of the causes of problems in Jatiluhur AMDK, especially for company employees. The subjects of this study were 18 employees in the production department. The workload measured is physiological and psychological. The physiological workload is measured based on the cardiovascular load (CVL) method, and the NASA measures psychological workload –Task Load Index (NASA– TLX) method. The purpose of this study was to determine the classification of physiological and psychological workloads in Jatiluhur AMDK and the causes of these physiological and psychological workloads. Based on the CVL analysis results, the number of employees who received a physiological workload that needed improvement was 10 out of 18 employees, with the highest percentage of 38.43% and the lowest of 21.73%. Very high work, 12 employees with a high category. With a percentage of 33.33% for very high workloads and 66.67% for high workloads.